Prevalence and clinical association of gene mutations through multiplex mutation testing in patients with NSCLC: results from the ETOP Lungscape Project. (23rd November 2017) - Kerr, K M; Dafni, U; Schulze, K; Thunnissen, E; Bubendorf, L; Hager, H; Finn, S; Biernat, W; Vliegen, L; Losa, J H; Marchetti, A; Cheney, R; et al.
Abstract: Background: Reported prevalence of driver gene mutations in non-small-cell lung cancer (NSCLC) is highly variable and clinical correlations are emerging. Using NSCLC biomaterial and clinical data from the European Thoracic Oncology Platform Lungscape iBiobank, we explore the epidemiology of mutations and association to clinicopathologic features and patient outcome (relapse-free survival, time-to-relapse, overall survival). Methods: Clinically annotated, resected stage I–III NSCLC FFPE tissue was assessed for gene mutation using a microfluidics-based multiplex PCR platform. Mutant-allele detection sensitivity is >1% for most of the ∼150 (13 genes) mutations covered in the multiplex test. Results: Multiplex testing has been carried out in 2063 (76.2%) of the 2709 Lungscape cases (median follow-up 4.8 years). FFPE samples mostly date from 2005 to 2008, yet recently extracted DNA quality and quantity was generally good. Average DNA yield/case was 2.63 µg; 38 cases (1.4%) failed QC and were excluded from study; 95.1% of included cases allowed the complete panel of mutations to be tested. Most common were KRAS, MET, EGFR and PIK3CA mutations with overall prevalence of 23.0%, 6.8%, 5.4% and 4.9%, respectively. KRAS and EGFR mutations were significantly more frequent in adenocarcinomas: PIK3CA in squamous cell carcinomas. MET mutation prevalence did not differ between histology groups. EGFR mutations were found predominantly in never smokers; KRAS in current/former smokers. For all the above mutations, there was no difference in outcome between mutated and non-mutated cases. Conclusion: Archival FFPE NSCLC material is adequate for multiplex mutation analysis. In this large, predominantly European, clinically annotated stage I–III NSCLC cohort, none of the mutations characterized showed prognostic significance.